Sweet potato for profit and health initiative (SPHI) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project seeks to reduce child malnutrition and improve smallholder incomes through the effective production and expanded use of sweet potato. It aims to build consumer awareness of sweet potato’s nutritional benefits, diversify its use, and increase market opportunities, especially in expanding urban markets of Sub-Saharan Africa. It involves the establishment of technical support platforms based in leading national programs in Uganda, Mozambique, and Ghana that serve as resource and training centers for both research and development of stakeholders and to establish a sweet potato community of practice.